Long-term changes in sexual functions following complicated pregnancies and deliveries. Issue 4 (2013) - Özler, Ali; Evsen, Mehmet Sıddık; Em, Pınar; Turgut, Abdulkadir; Başaranoğlu, Serdar; Bez, Yasin; Yalınkaya, Ahmet; Gül, Talip
No abstract available